2011
DOI: 10.4049/jimmunol.1100794
|View full text |Cite
|
Sign up to set email alerts
|

NKT TCR Recognition of CD1d-α-C-Galactosylceramide

Abstract: NKT cells respond to a variety of CD1d-restricted glycolipid antigens that are structurally related to the prototypic antigen, α-galactosylceramide (α-GalCer). A modified analogue of α-GalCer with a carbon-based glycosidic linkage (α-C-GalCer) has generated great interest because of its apparent ability to promote prolonged, Th1-biased immune responses. Here we report the activation of spleen NKT cells to α-C-GalCer, and related C-glycoside ligands, is weaker than that of α-GalCer. Furthermore, the Vβ8.2 and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 39 publications
3
53
0
1
Order By: Relevance
“…The substantial stability of 10 itself and its ability to activate NK cells might make for large scale IFNproduction. 70) Although X-ray analysis of mouse CD1d/ 10/TCR has been reported, 69,116) the key factor arousing the Th1-type response has not been clarified yet. The progress of further investigation is expected with anticipation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substantial stability of 10 itself and its ability to activate NK cells might make for large scale IFNproduction. 70) Although X-ray analysis of mouse CD1d/ 10/TCR has been reported, 69,116) the key factor arousing the Th1-type response has not been clarified yet. The progress of further investigation is expected with anticipation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on X-ray information on mouse and human CD1d/1/TCR complexes, [22][23][24] the spatial relationship between the galactose and the ceramide parts appears to be very important in making a rigid complex with CD1d that shows potent bioactivities. 69) Chen et al reported the synthesis of -galactosylated oxime analog 17, which is also an elongated analog having an extra N-atom, without biological information, in 2010. 83) 3.…”
Section: )mentioning
confidence: 99%
“…Besides NKT-like cells, a small proportion of Type I NKT (iNKT) cells are CD56+ (40,41). The discrimination between these two (iNKT & NKT-like) subsets requires the use of CD1d loaded with α-GalCer (α-galactosylceramide) (42), lacking in our research. Thus, at this level, we could not determine the type of NKT cells in the patients and controls, and so we reported our results as CD3+CD56+ NKT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, el compuesto α-C-GalCer (tabla 1), que tiene un remplazo del oxígeno de unión al azúcar por un carbono, produce una respuesta con tendencia al tipo Th1 (28). Un efecto similar se ha observado con el cambio de un oxígeno por un carbono en la galactosa para crear el compuesto llamado carbasugar (RCAI-56) (17).…”
Section: Antígenos Lipídicos Sintéticosunclassified